The Principal Role of Chorus Ducting for Night‐Side Relativistic Electron Precipitation - Kang, Ning; Artemyev, Anton V.; Bortnik, Jacob; Zhang, Xiao‐Jia; Angelopoulos, Vassilis (Geophysical research letters, 2024)
Night‐side chorus waves are often observed during plasma sheet injections, typically confined around the equator and thus potentially responsible for precipitation of ≲100 keV electrons. However, recent low‐altitude observations have revealed the critical role of chorus waves in scattering relativistic electrons on the night‐side. This study presents a night‐side relativistic electron precipitation event induced by chorus waves at the strong diffusion regime, as observed by the ELFIN CubeSats. Through event‐based modeling of wave propagation under ducted or unducted regimes, we show that a density duct is essential for guiding chorus waves to high latitudes with minimal damping, thus enabling the strong night‐side relativistic electron precipitation. These findings underline both the existence and the important role of density ducts in facilitating night‐side relativistic electron precipitation. Plain Language Summary Chorus waves, an important mode of electromagnetic waves in Earth's magnetosphere, play a vital role in scattering energetic electrons (electron precipitation) in the radiation belts. It has been shown in observations that night‐side chorus waves usually remain confined near their equatorial source and thus do not significantly affect relativistic electron precipitation. However, recent observations challenge this notion, suggesting a viable connection between the night‐side relativistic electron precipitation and chorus waves. In this work, we present an event observed on the ELFIN CubeSats that reveals intense relativistic electron precipitation on the night‐side, where the ratio between precipitation and trapped fluxes reaches the theoretical maximum of 1. To investigate the physical mechanism responsible for this event, we used numerical modeling to simulate scenarios with and without a density‐enhancement duct along magnetic field lines. Our results show that such ducts can efficiently trap chorus waves and guide them to high latitudes without significant damping where they can efficiently interact with the relativistic electrons. By comparing the precipitation intensity in ducted and unducted cases, we affirm the crucial role of density ducts in driving strong night‐side relativistic electron precipitation. Key Points We present observations of night‐side relativistic electron precipitation induced by whistler‐mode waves We perform a comparison of observations with simulation results for different wave propagation regimes We show that only ducted whistler‐mode waves can effectively scatter relativistic electrons on the night‐side